Metropolitan Governance in Brazil : Inputs for an Agenda and Strategy - World Bank Group (World Bank, Washington, DC, 2015)
In less than fifty years, Brazil evolved from a predominantly rural society and economy to a highly urbanized country in which 85 percent of its people now live in urban areas and more than 90 percent of the country’s GDP is generated in the cities. This rapid urbanization process was characterized by a lack of planning and an enduring framework of inequality, resulting in high degrees of concentrated poverty in the urban areas. Much of this urbanization has taken place in metropolitan regions (MRs). MRs have grown more rapidly than the rest of the country, both in population and in GDP terms. In 2010, per capita GDP was higher in MRs than in the rest of the country and metropolitan economies accounted for 70 percent of GDP. At the same time, half of the Brazilian poor and 90 percent of the people living in subnormal conditions were found in metropolitan regions. The recent approval of a new framework for metropolitan governance inBrazil creates the opportunity for debate and evolution regarding several key issues. These include: a) placing metropolitan matters at the forefront of the development arena in Brazil; b) reviewing what has been learned about inter-municipal governance and service delivery; c) estimating resource mobilization needs for metropolitan development; d) coordinating metropolitan land use with transport and housing; e) including metropolitan concerns in any revision of fiscal federalism; and f) promoting environmental sustainability, social inclusion and resilience to disasters and climate change plans at the metropolitan scale. The World Bank can be a partner in addressing these issues. In responding to client demand, the Bank has been providing a range of support to Brazilian states and cities and especially their low- income populations in the areas of infrastructure, social services, slum upgrading, institutional development, river basin management, local economic development, environmental protection, water and sanitation, and transportation.